2017
DOI: 10.1002/mus.25658
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of systemic gene therapy in a canine model of myotubular myopathy

Abstract: Introduction X-linked myotubular myopathy (XLMTM), a devastating pediatric disease caused by the absence of the protein myotubularin, results from mutations in the MTM1 gene. While there is no cure for XLMTM, we previously reported effects of MTM1 gene therapy using adeno-associated viral (AAV) vector on muscle weakness and pathology in MTM1-mutant dogs. Here, we followed 2 AAV-infused dogs over 4 years. Methods We evaluated gait, strength, respiration, neurological function, muscle pathology, AAV vector cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…It is possible that the development of structural changes and, consequently, clinically significant manifestations of myotubularin deficiency outside of the muscular system reflect variations in gene mutations. In this era of gene‐targeted and gene‐replacement trials and therapies, understanding of myotubularin gene modification and protein function in other tissues is crucial when studying outcomes and determining risks and benefits . Further exploration of myotubularin function in pneumocytes may also provide insight into the pathophysiology of peliosis hepatis and the associated endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the development of structural changes and, consequently, clinically significant manifestations of myotubularin deficiency outside of the muscular system reflect variations in gene mutations. In this era of gene‐targeted and gene‐replacement trials and therapies, understanding of myotubularin gene modification and protein function in other tissues is crucial when studying outcomes and determining risks and benefits . Further exploration of myotubularin function in pneumocytes may also provide insight into the pathophysiology of peliosis hepatis and the associated endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Recent preclinical studies of novel therapeutic approaches, including gene replacement using an adeno‐associated viral vector, have brought XLMTM to the forefront of translational science . Coupled with extended survival, due to shared decisionmaking and technological supports, providers are now recognizing additional myotubularin‐related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Current and future therapeutic approaches to congenital myopathies are elaborated in other reviews . Gene therapy trials are evolving, in particular in X‐linked myotubular myopathy . Recently, the effects of MTM1 gene therapy using an AAV8 vector have been demonstrated in MTM1 ‐mutant dogs with obvious long‐term advantages on muscle weakness and pathology .…”
Section: Pathogenesis Of Congenital Myopathies and Emerging Therapiesmentioning
confidence: 99%
“…In this issue of Muscle & Nerve , Elverman et al . report follow‐up data from XLMTM dogs that received quasi‐systemic AAV8‐ MTM1 treatment 4 years ago.…”
mentioning
confidence: 99%
“…The Childers laboratory has shown that AAV8 is a suitable vector, is well tolerated, corrects muscle pathology, and can impact survival with significant long‐term clinical effects . Some evidence, in the form of slightly decreased muscle strength, focal reversion of pathology, and diminished myotubularin expression, indicated that the effects of a single treatment can wane.…”
mentioning
confidence: 99%